2013
DOI: 10.1371/journal.pone.0077914
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Atrophy and Functional Connectivity Changes Related to Fatigue in Multiple Sclerosis

Abstract: Fatigue is one of the most frequent symptoms in multiple sclerosis (MS), and recent studies have described a relationship between the sensorimotor cortex and its afferent and efferent pathways as a substrate of fatigue. The objectives of this study were to assess the neural correlates of fatigue in MS through gray matter (GM) and white matter (WM) atrophy, and resting state functional connectivity (rs-FC) of the sensorimotor network (SMN). Eighteen healthy controls (HCs) and 60 relapsing-remitting patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 39 publications
6
93
1
2
Order By: Relevance
“…Another study also showed no difference in 18 F‐dopa uptake between 10 fatigued PD subjects and 10 nonfatigued PD subjects but revealed serotonin transporter binding in the caudate, putamen, ventral striatum, and thalamus was decreased in fatigued compared with nonfatigued patients . The role of other neurotransmitter systems (eg, norepinephrine, acetylcholine GABA, glutamate), morphologic changes in gray and white matter, and regional brain activity and functional connectivity have yet to be explored in PD‐related fatigue but are associated with fatigue in other neurologic disorders and should be pursued …”
Section: Working Group Strategymentioning
confidence: 99%
“…Another study also showed no difference in 18 F‐dopa uptake between 10 fatigued PD subjects and 10 nonfatigued PD subjects but revealed serotonin transporter binding in the caudate, putamen, ventral striatum, and thalamus was decreased in fatigued compared with nonfatigued patients . The role of other neurotransmitter systems (eg, norepinephrine, acetylcholine GABA, glutamate), morphologic changes in gray and white matter, and regional brain activity and functional connectivity have yet to be explored in PD‐related fatigue but are associated with fatigue in other neurologic disorders and should be pursued …”
Section: Working Group Strategymentioning
confidence: 99%
“…This phenomenon has been attributed to a failure of intracortical inhibition (ICI) in frontal and M1 areas, both before and after fatiguing exercises ( 4 ). Furthermore, structural and functional data report a parietal involvement in MS fatigue symptoms ( 7 9 ), with indications of a reduced primary somatosensory area (S1) excitability ( 10 , 11 ), and tDCS has been reported to enhance parieto-frontal projections ( 12 ). Also, in previous works of ours, we noticed signs of impaired communication between S1 and M1 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…b): Links indicate interregional connectivity. Indeed, the heterogeneous patterns of functional connectivity alterations in MS include abnormalities between interoceptive areas, such as the ACC and the insula(Faivre et al, 2012;Rocca et al, 2015;Roosendaal et al, 2010), alongside disruptions in relevant anatomical pathwaysfor example, the ACC white matter bundle within the left cingulate fasciculus (CruzGomez, Ventura Campos, Belenguer, Avila, & Forn, 2013;Pardini et al, 2015). Colors indicate statistically significant differences (p < .05; green = interoception > mind wandering; red = MS patients > controls; black = no significant differences).…”
mentioning
confidence: 99%